Unique Stimuli Responsive Characteristics Of Electron Beam Synthesized Bacterial Cellulose/acrylic Acid Composite - Nadia Halib; Mohd Cairul Iqbal Mohd Amin; Ishak Ahmad (Wiley Periodicals, Inc., 2024)
The formation and swelling behavior of bacterial cellulose/acrylic acid hydrogel prepared from aqueous mixture consists of 20 : 80 (v/v) acrylic acid (AAc) and 1% bacterial cellulose dispersion under accelerated electron beam was investigated. Gel fraction of hydrogel increased with the increasing dose suggesting a denser composite at 50 kGy compared to 35 kGy. SEM photomicrographs revealed a homogenous pores distribution at higher dose with pore sizes ranging from 1 to 5 μm. Hydrogel synthesized at lower dose of electron beam exhibited higher swelling ability and the degree of swelling increased as the pH of surrounding medium increased and it reached the optimum swelling at pH 7. While swelling of the hydrogel decreased with the increasing ionic strength of solution, swelling at different temperatures ranging from 25 to 50°C revealed a unique character where the hydrogel shrunk at 37°C. Moreover, hydrogel synthesized at higher dose exhibited a higher degree of swelling in methanol with respect to water. © 2010 Wiley Periodicals, Inc. J Appl Polym Sci, 2010